CHEMICAL ECOLOGY OF MARINE CYANOBACTERIAL SECONDARY METABOLITES: A MINI-REVIEW - Lik Tong Tan; Beverly Pi Lee Goh (JOURNAL OF COASTAL DEVELOPMENT, 2009)
More than 300 nitrogen-containing secondary metabolites have been reported from the procaryotic marinecyanobacteria. A majority of these compounds are of the polypeptide or mixed polyketide-polypeptidestructural class and they are a potential source of novel pharmaceuticals. In spite of the chemical richnessof marine cyanobacteria, not much is known regarding their ecological functions. To date only a handful ofmarine cyanobacterial compounds have been examined for their involvement in predator-prey interactions.This mini-review surveys the various chemical ecology studies conducted on marine cyanobacterialcompounds. From these ecological studies, many marine cyanobacterial compounds are known to deterfeeding by several species of marine predators. Such chemical defense may be crucial in maintaining thepopulation of marine cyanobacterial bloom in nature. In addition, a series of ecological studies from ourlaboratory revealed the anti-settlement properties of a number of benthic marine cyanobacterialcompounds. These studies suggested marine cyanobacteria as a potential source of natural antifoulants forthe control of fouling organisms.